Role of Principal as Innovator, Motivator, and Collaborator in the Implementation of School-Based Management - Sutrisna, Tri harto Eka; Eko Pramono, Suwito; Supraptono, Eko (Educational Management, 2021)
The purpose of this study was to describe and analyze the role of the principal as an innovator, motivator, and collaborator in the implementation of school-based management at SMP Nasima Semarang. This research approach is a qualitative approach with a holistic descriptive. Data were collected through interviews, observation, and documentation. Informants in this research were principals, vice principals, teachers, and school committees. The results of this study indicate that the role of the principal as an innovator, motivator, and collaborator in the implementation of school-based management at SMP Nasima Semarang is (1) as an innovator must have different, unique, and superior ideas (2) as a motivator must have a strategy in providing education ( 3) as collaborators must be able to involve all parties in providing education (4) the ability of school principals to manage professionally is the key to the successful implementation of school-based management (5) the participation of all parties results in transparency and accountability of parents of students towards the implementation of education